ANALISIS EFISIENSI KERJA DAN NILAI DEPRESIASI ALAT GALI MUAT MENGGUNAKAN METODE DEPRESIASI GARIS LURUS - Purwandari, Diana; Kurniadi, Waspada; Maulana, Muhammad Ravli (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2025)
This research aims to analyze the work efficiency of use of loading digging equipment, namely excavators, using the straight line depreciation method to determine the residual value of the equipment after 7 years of depreciation and the productivity value of the equipment after 12 years of use. An excavator loading digging tool with a bucket capacity of 1,1 m3 has an average circulation time of 2,08 minutes with an average productivity of 22,86 m3/hour or 205,74 m3/day. Excavator operational costs are Rp70.208.980,81 in 1 month, with a work efficiency value of 86.40% this shows that the work efficiency of the excavator is quite good. The acquisition price of the excavator is calculated at Rp1.119.402.985,00, so the annual depreciation value of the excavator using the straightline depreciation method is Rp127.931.769,71, with a residual value at the end of year 7 of Rp223.880.597,00, so that at the end year 8 has a residual value of Rp95.948.827,29. In reality, excavators with a usage duration of up to 12 years still have an average productivity of 5349.55 m3/month and can still meet the company's target of 5.000 m3/month.